Novel functions of the MOZ double PHD finger domain - Deeves, Sian Elizabeth (2012)
Monocytic leukaemia zinc-finger protein (MOZ) is a histone acetyltransferase (HAT) implicated in haematopoiesis and acute myeloid leukaemia, as well as embryonic and postnatal development. MOZ contains multiple domains, including a MYST HAT domain and a double PHD finger domain (DPF) suggesting it interacts with histones. This work has established for the first time that the MOZ DPF exhibits dual functionality in establishing and sensing post-translational modifications (PTMs) of histones. Firstly, our data detected the direct interaction of MOZ with the N-terminal tails of histones H3 and H4 and shows that the MOZ DPF domain mediates such binding. Both PHD fingers are required and functionally cooperate to establish the DPF histone binding preference in terms of PTMs. We demonstrate that H3K4me3 prevents MOZ DPF association with H3, although H3K4me2 is tolerated. Similarly, H4Kac acts as a dominant exit signal that excludes MOZ from chromatin. This ability to sense H3K4 PTM status was confirmed in a collaborative effort establishing the crystal structure of MOZ DPF in complex with an unmodified H3 peptide. The H3 peptide adopted an α-helical conformation in the complex, which has not previously been observed.